The regional impact of cultural diversity on wages: Evidence from Australia - Amanuel Elias; Yin Paradies (IZA Journal of Migration, 2016)
This paper investigates the impact of cultural diversity on labour market outcomes, particularly on wages across regions using a large longitudinal data. We apply an instrumental variable approach and account for individual and time fixed effects. Our findings indicate that the current level of cultural diversity positively affected current regional weekly wages; however, the positive effect holds only partially when the diversity is lagged. The results appear to be robust in all estimations controlling for heterogeneity factors and accounting for the self-selection of individuals into places with better economic opportunities. Our findings concerning the effect of lagging on the effect of diversity may explain the variation in the literature where some studies report that cultural diversity increases wages across time while others do not.
Keywords: J61; R23; Z19; 330; Cultural diversity; Wages; Instrumental variable; Shift-share; Australia